Recent advances in the pharmacotherapeutic management of diabetic kidney disease. (3rd May 2022) - Block, Tomasz J.; Batu, Duygu; Cooper, Mark E.
ABSTRACT: Introduction: Diabetic kidney disease (DKD) remains a major cause of morbidity and mortality in diabetes and is a key cause of end-stage kidney disease (ESKD) worldwide. Major clinical advances have been confirmed in large trials demonstrating renoprotection, adding to the benefits of existing intensive glucose and blood pressure control therapies. Furthermore, there are exciting new treatments predominantly at an experimental and early clinical phase which appear promising. Areas covered: The authors review DKD in the context of existing and emerging therapies affording cardiorenal benefits including SGLT2 inhibitors and GLP-1 receptor agonists. They explore novel therapies demonstrating potential including a newly developed mineralocorticoid receptor antagonist and endothelin receptor blockade, while evaluating the utility of DPP4 inhibitors in current clinical practice. They also consider the recent evidence of emerging therapies targeting metabolic pathways with enzyme inhibitors, anti-fibrotic agents, and agents modulating transcription factors. Expert opinion: Significant improvements have been made in the management of DKD with SGLT2i and GLP-1 agonists providing impressive renoprotection, with novel progress in renin–angiotensin–aldosterone system (RAAS) blockade with finerenone. There is also great potential for several new experimental therapies. These advances provide us with optimism that the outlook of this devastating condition will continue to improve.